Nutritional repercussions of the use of maternized milks in infants 'health (Research, Society and Development, 2020)
The present work aims to identify the nutritional repercussions of the use of maternal formulas on the health of infants, analyzing the composition of the most used milks, pointing out differences between infant formulas and human milk. This is a cross-sectional, qualitative and quantitative descriptive study on the topic, where information was obtained through the analysis of the labels of maternal milk and comparison with the nutritional composition of human milk, the parameters of the world health organization (WHO) and the literature on the subject in question. Regarding the total calories, it was observed that the formulas have a greater amount than in colostrum and less in the other phases of milk in brands A and B. As for macronutrients, the amount of proteins was lower in milk formulas when compared to colostrum and higher in milk formulas compared to transitional and mature milk. In relation to lipids and carbohydrates, the amounts in milk formulas were higher in the two brands converging to human milk, in its three phases. It is concluded that, the most suitable food for the infant is breastfeeding, since the formulas show risk factors for the babies' health, such as: diarrhea, possible losses in growth and development. Thus, the replacement of human milk should only be indicated when it cannot be administered, and this indication is performed by professionals.